The Routes Muslim Merchants Used for Maritime Trade with China in the Middle Ages - İbrahim Güneş (Türkiyat Mecmuası)
Maritime trade with India and China by means of Basrah and Suez, which had great importance during the Sassanid-Byzantine struggle, increased its importance with the birth of Islam. These trade routes used to surround the Arabian Peninsula in two routes one through Basrah and the other through Clysma (al-Kulzum) before coming together in Hormuz. Merchants then would follow this route to do their trade from centers starting in Hormuz and going to India, Sind (Indo-China), and China, bringing various kinds of precious stones, silk fabrics, patterned vases, porcelain, spices, and exotic fruits that were then sold in Islamic countries. Sources from the period noted these routes’ interconnections to be important points in the maritime transport that took place between the East and West. A great wealth of records are found on the subject in many sources of the period, especially in medieval geographical works, and Muslim merchants are understood from these records to have gone to China to buy goods and sell them in their own countries. This maritime trade actually experienced its most active period during the Abbasid dynasty (750-1258 CE), and allowed the Islamic world to encounter, influence, and be influenced by Indian and Chinese civilizations. This article the important routes of this maritime trade that had been actively used starting from Suez and Basra in the west and ending in the Canton region of China along the Indian coast in the east light of the data provided by authors from the Middle Ages. The records in the sources of the period have also been referenced here.